2016
DOI: 10.1124/mol.115.101949
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Phosphorylation Clusters Determine the Signaling Outcome of Free Fatty Acid Receptor 4/G Protein–Coupled Receptor 120

Abstract: It is established that long-chain free fatty acids including v-3 fatty acids mediate an array of biologic responses through members of the free fatty acid (FFA) receptor family, which includes FFA4. However, the signaling mechanisms and modes of regulation of this receptor class remain unclear. Here, we employed mass spectrometry to determine that phosphorylation of mouse (m) FFAR4 occurs at five serine and threonine residues clustered in two separable regions of the C-terminal tail, designated cluster 1 (Thr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 49 publications
4
66
0
Order By: Relevance
“…We recently defined the sites of agonist-regulated phosphorylation within the C-terminal tail of both mouse (m)FFA4 and human (h)FFA4 and defined that conversion of these serine and threonine residues to alanines produces phosphorylation-deficient (PD) forms of the receptor orthologs (21, 22). We also recently proposed that detection of agonist-regulated GPCR phosphorylation using phospho-specific antibodies could be used as a biomarker for receptor activation (24).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently defined the sites of agonist-regulated phosphorylation within the C-terminal tail of both mouse (m)FFA4 and human (h)FFA4 and defined that conversion of these serine and threonine residues to alanines produces phosphorylation-deficient (PD) forms of the receptor orthologs (21, 22). We also recently proposed that detection of agonist-regulated GPCR phosphorylation using phospho-specific antibodies could be used as a biomarker for receptor activation (24).…”
Section: Resultsmentioning
confidence: 99%
“…We also recently proposed that detection of agonist-regulated GPCR phosphorylation using phospho-specific antibodies could be used as a biomarker for receptor activation (24). Here we used phospho-specific antibodies against the agonist-regulated phosphorylation sites Thr 347 and Ser 350 (21, 22) as a marker for FFA4 activation in genome-edited HEK293 cells. After stable expression of mFFA4-eYFP in each of parental HEK293 cells and the Gα q /Gα 11 or arrestin2/3 genome-edited cell lines and selection of individual clones, activation of mFFA4 by the agonist TUG-891 (2527) was produced no-matter the genetic status of the cells (parental or genome-edited) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes in receptor conformation are detected by G protein-coupled receptor kinases (GRKs), resulting in specific phosphorylation patterns at receptor intracellular domains. Quantitative mass spectrometry approaches, combined with phosphospecific antibodies, have shown that ligand-induced receptor phosphorylation is tissue and ligand specific and can be associated with specific signaling cascades; this supports a phosphorylation barcode hypothesis (Butcher et al, 2011;Liggett, 2011;Nobles et al, 2011;Prihandoko et al, 2016). Receptor phosphorylation is recognized by b-arrestins, which are recruited to the plasma membrane and sterically hinder G protein association while initiating b-arrestin-mediated internalization and signaling (Nobles et al, 2011;Liggett, 2011).…”
Section: Cb 1 Rs and B-arrestin-mediated Signalingmentioning
confidence: 92%
“…These bar-codes are finely tuned and define which signaling cascades are activated, thus opening up a spectrum of possibilities frequently defined as functional selectivity or ligand bias (Liggett, 2011; Nobles et al, 2011; Prihandoko et al, 2016). However, careful consideration must be taken when interpreting results obtained from heterologous systems, particularly when signaling can be significantly affected (biased) by the different levels of protein expression across different cell types (Bosier et al, 2010; Atwood et al, 2011; Straiker et al, 2012).…”
Section: The Endocannabinoid System In the Cnsmentioning
confidence: 99%